PENGARUH KUALITAS PELAYANAN, TARIF DAN FASILITAS TERHADAP KEPUASAN PELANGGAN - Rauna Islamunissa Susanto; Bambang Sutikno; Ascosenda Ika Rizqi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
In the modern age, it is increasingly trend to care for such animals as cats and dogs. This causes health services to compete to be competitive. Customer satisfaction is an important aspect of business success. Customer satisfaction is obtained by improving the service quality, tariffs and facilities. This study aimed to find out the effect of service quality, tariffs and facilities at the Drh. Fitri Hamidah clinik in Pasuruan city to customer satisfaction. This study, using quantitative research methods and 75 respondents take samples. Data collection techniques carried out through library research, observation, interviews and questionnaires. The data analysis technique used is descriptive analysis, instrument test, classic assumption test, multiple linear regression, hypothesis test and coefficient of determination test (Adjusted R2). The results showed that there was a contribution of the independent variable to the dependent variable of 76,9% with the results of the calculated F Test > F table, namely 83,291 > 2,74 which explains service quality (X1), tariff (X2) and facilities (X3) have positif dan significant impact on customer satisfaction (Y). The t-test of the variable service quality (X1) have positif dan significant impact on customer satisfaction (Y) with value t count > t table, which is 6.992 > 1.66. The t-test results on the variable tariff (X2) have positif dan significant impact of customer satisfaction (Y) with value t count > t table, which is 4.079 > 1.66. Whereas the results of the variable facilities (X3) have positif dan significant impact on customer satisfaction (Y) with t count > t table, which is 10.546 > 1.66